Ashwagandha: Most of desired COVID-19 immunobooster medicinal plant - Das, Manish; Singh, A K (Indian Horticulture, 2022)
Ashwagandha (Withania somnifera (L.) Dunal) belongs to family Solanaceae, and is one of the popular and highly valued medicinal herbs in Ayurveda, classified as a rasayana (rejuvenator) in various Ayurvedic classical texts. Various parts of the plant are used in the preparation of different Ayurvedic formulations and home remedy recipes to increase health and longevity. This herb is always on demand, however, demand has risen further due to its immunoboosting capacity which would be a great therapy for fighting COVID-19 like situation. The word Ashwagandha has been derived from Sanskrit name "Ashwa" meaning horse and "gandha" meaning smell and thus given to this plant due to the smell of the roots resembling a sweating horse. Root is the economic part of this crop. The roots are frequently used for therapeutic purposes and is a constituent of over 200 formulations in Ayurveda, Siddha and Unani medicines. There are several reports to establish its immune-modulatory, anti-inflammatory, anti-stress, memory enhancing, antiparkinsonian, hypolipidemic, antibacterial, cardiovascular, antioxidant, antitumor and adaptogenic properties. Ashwagandha plants are multiplied through seeds. Some significant work has been carried out by ICAR-DMAPR, Anand on seed germination and crop improvement including developing chemotypes.